The use of natural gas as fuel for motorcycles - Abdul Majid, Zulkifli; Yaacob, Zulkefli; Ahmad Khan, Yasmin (Gasteg, 2006)
Utilization of motorcycle in Malaysia is really synonym especially for lower income group. Statistic for motor vehicles in Malaysia shown that nearly five million units or over the half are motorcycles. These are mostly small capacity, two or four stroke engine motorcycles. The use of low quality fuel to operate motorcycles causes a serious pollutant especially in densely populated areas. Besides, crude oil reserve in Malaysia is expected to finish within 19 years. Natural gas is now acknowledged by the world as being a mainstream alternative fuel. It has a high octane rating that is general indication of the ability of the fuel to burn more efficient and improving engine performance. Malaysia has massive, under exploited natural gas reserve. As such a study has been conducted by a group of researchers from Gas Technology Centre (GASTEG) to diversify the usage of natural gas especially as a fuel for internal combustion engine. The product of this research is a set of natural gas conversion kits and the first prototype of natural gas motorcycle. The exhaust emissions from natural gas motorcycle give complete combustion, which decrease 99.6% of carbon monoxide and 72.5% of unburned hydrocarbon at a speed of 70km/hr. However, the lower heat content of natural gas and the lower burning velocity as compared to gasoline reduces the engine maximum power for about 15% at high engine speed without any modification to the original engine. These parameters can be used as a guidance to the motorcycle industry how to utilise natural gas as a fuel, a new and a leading technology for the world that propelling Malaysia for the next millennium with clean city.